2021
DOI: 10.3389/fmats.2021.656261
|View full text |Cite
|
Sign up to set email alerts
|

Influence on Polyurethane Synthesis Parameters Upon the Performance of Base Asphalt

Abstract: The objective of this study aims to investigate the performance of thermoplastic polyurethane elastomers (TPU)-modified asphalt, with special focus on the influence of polyurethane synthesis parameters upon the performance of base asphalt. In this study, the TPU modifier was incorporated into base asphalt to prepare TPU-modified asphalt by using a self-determined laboratory process. The properties of polyester-based TPU and polyether-based TPU modified asphalt with different contents was analyzed by the base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Salas et al [ 27 ] used PU foam to prepare PU-modified asphalt and found that, in comparison to conventional polymer-modified asphalt mixtures, PU-modified asphalt has improved stability and low-temperature deformability. Jin et al [ 28 ] used TPU as a modifier to be incorporated into base asphalt and found that TPU-modified asphalt had better properties, such as ductility, softening point, needle penetration, and rotational viscosity after the experimental analysis of the chemical, microstructural, and rheological properties of the modified asphalt, and pointed out that polyester-based TPU modifiers have better high-temperature properties than polyether-based TPU modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Salas et al [ 27 ] used PU foam to prepare PU-modified asphalt and found that, in comparison to conventional polymer-modified asphalt mixtures, PU-modified asphalt has improved stability and low-temperature deformability. Jin et al [ 28 ] used TPU as a modifier to be incorporated into base asphalt and found that TPU-modified asphalt had better properties, such as ductility, softening point, needle penetration, and rotational viscosity after the experimental analysis of the chemical, microstructural, and rheological properties of the modified asphalt, and pointed out that polyester-based TPU modifiers have better high-temperature properties than polyether-based TPU modifiers.…”
Section: Introductionmentioning
confidence: 99%